Whole exome sequencing of patients with varicella-zoster virus and herpes simplex virus induced acute retinal necrosis reveals rare disease-associated genetic variants - Heinz, Johanna L.; Swagemakers, Sigrid M. A.; von Hofsten, Joanna; Helleberg, Marie; Thomsen, Michelle M.; De Keukeleere, Kerstin; de Boer, Joke H.; Ilginis, Tomas; Verjans, Georges M. G. M.; van Hagen, Peter M.; van der Spek, Peter J.; Mogensen, Trine H. (Frontiers in Molecular Neuroscience, 2023)
Purpose: Herpes simplex virus (HSV) and varicella-zoster virus (VZV) are neurotropic human alpha herpesviruses endemic worldwide. Upon primary infecon, both viruses establish lifelong latency in neurons and reacvate intermitently to cause a variety of mild to severe diseases. Acute renal necrosis (ARN) is a rare, sight-threatening eye disease induced by ocular VZV or HSV infecon. The virus and host factors involved in ARN pathogenesis remain incompletely described. We hypothesize an underlying genec defect in at least part of ARN cases.We collected blood from 17 paents with HSV-or VZV-induced ARN, isolated DNA and performed Whole Exome Sequencing by Illumina followed by analysis in Varseq with criteria of CADD score > 15 and frequency in GnomAD >0.1% combined with biological filters. Gene modificaons relave to healthy control genomes were filtered according to high quality and read-depth, low frequency, high deleteriousness predicons and biological relevance.We idenfied a total of 50 potenally disease-causing genec variants, including missense, frameshi and splice site variants and on in-frame deleon in 16 of the 17 paents. The vast majority of these genes are involved in innate immunity, followed by adapve immunity, autophagy, and apoptosis; in several instances variants within a given gene or pathway was idenfied in several paents.We propose that the idenfied variants may contribute to insufficient viral control and ocular disease presentaon in the paents and serve as a knowledge base and starng point for the development of improved diagnosc, prophylacc, and therapeuc applicaons.